Simultaneous Determination of Ten Nutrient Elements in the Leaf of Gannan Navel Oranges from Southern Jiangxi by ICP-AES with Microwave Digestion - Xue, Jun; Liu, Jing-Yi; Fan, Yu-Lan; Li, Xun (Asian Journal of Chemistry, 2012)
A method for the simultaneous determination of Mn, Fe, Cu, Zn, K, Ca, Mg, P, B and S in leaf of navel oranges in southern Jiangxi by inductively coupled plasma-atomic emission spectroscopy (ICP-AES) after H2O2-HNO3 microwave digestion was established. The method was verified by the determination of the reference materials (GBW10020). Values of detection limit of elements found were in the range of 0.15-76.8 μg L-1. The proposed method was used in the analysis of navel orange leaves sample, giving values of RSD (n = 5) for the 10 elements in the range of 0.63-2.89 % and values of recovery in the range of 91.0-109.8 %. Leaf samples from 10 navel orange orchards were analyzed. The results show that the macronutrients K and P were higher than the corresponding suitable levels and the nutrients Ca, Zn, Cu and Mg were in low range. Therefore, the problems in fertilizer application in southern Jiangxi navel orange orchards were insufficient or excessive fertilizer application.